Koneksi Matematis Mahasiswa Kaitannya dengan Folding Back dalam Menyelesaian Masalah Kesamaan Dua Fungsi - Fitri Umardiyah; Mashuda Mashuda (JoEMS (Journal of Education and Management Studies), 2019)
This research is to describe student’s mathematical connection with “folding back” when solving the problem of the similarity between two functions. The research method uses a fixed comparison method. Subjects at this research is students who experienced folding back when solving two similarity problems. Data is the form of solving the problem and the results of the interview related to the settlement. Based on the results of the data analysis it was concluded: first, student’s folding back from the level of understanding of formalising about the similarity of two functions to the level of understanding image making and connecting it with rational functions and linear functions. Students recognize the connection between the similarity of two functions with rational functions and linear functions but do not understand the interconnection of mathematical ideas and construct each other to produce a unity. Second, students remain at the level of understanding image making, recognizing the similarity between the two functions based on the form of function but not based on the similarity of definitions of two functions. Third, students can move from the level of understanding image making to the level of observing understanding to be able to distinguish two functions f and g because of invocative intervention. Students succees in making a connection between the similarity of two functions with the function value and understanding the concept of the similarity of two functions to be able to distinguish between the two functions f and g. Keywords: Matemathical Connection; Folding Back; Similarity of Two Function’s Problem